2023
DOI: 10.1002/ejhf.2920
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability and efficacy of up‐titration of guideline‐directed medical therapies for acute heart failure in elderly patients: A sub‐analysis of the STRONG‐HF randomized clinical trial

Abstract: AimsSTRONG‐HF examined a high‐intensity care (HIC) strategy of rapid up‐titration of guideline‐directed medical therapy (GDMT) and close follow‐up after acute heart failure (AHF) admission. We assess the role of age on efficacy and safety of HIC.Methods and resultsHospitalized AHF patients, not treated with optimal GDMT were randomized to HIC or usual care. The primary endpoint of 180‐day death or HF readmission occurred equally in older (>65 years, n = 493, 74 ± 5 years) and younger patients (53 ± 11 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Similar to other STRONG‐HF sub‐analyses, 9,10 variables used for covariate adjustment were selected from those most highly associated with each endpoint in the UC group of STRONG‐HF using backwards selection in the Cox regression model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other STRONG‐HF sub‐analyses, 9,10 variables used for covariate adjustment were selected from those most highly associated with each endpoint in the UC group of STRONG‐HF using backwards selection in the Cox regression model.…”
Section: Methodsmentioning
confidence: 99%
“…6 The STRONG-HF (Safety, Tolerability and Efficacy of Rapid Optimization, Helped by NT-ProBNP Testing, of Heart Failure Therapies) trial demonstrated that a high-intensity care (HIC) treatment strategy, characterized by rapid up-titration of oral medications for HF and close follow-up with multiple early ambulatory visits after an admission for AHF, improves quality of life and reduces the risk of 180-day all-cause death or HF rehospitalization, compared with usual care (UC). 8 This strategy was both safe and effective regardless of age, 9 sex, 10 left ventricular ejection fraction (LVEF) 11 or baseline N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels. 12 In clinical trial settings, there are relatively limited data to describe the impact of comorbidities on optimization of HF medical therapies and relationship between comorbidity burden and post-discharge clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a secondary analysis of the STRONG-HF trial, the high-intensity care (HIC) strategy was safe and significantly reduced all-cause mortality and HF readmission at 180 days compared to usual care without a significant interaction of age and sex. 40,41 However, older patients had smaller benefits in terms of quality of life. 40 The detection of B-lines through lung ultrasound (LUS) is of utmost importance for the diagnosis of congested acute HF.…”
Section: Post-heart Failure Hospitalization Carementioning
confidence: 99%
“…40,41 However, older patients had smaller benefits in terms of quality of life. 40 The detection of B-lines through lung ultrasound (LUS) is of utmost importance for the diagnosis of congested acute HF. A secondary analysis of the BLUSHED-AHF trial, designed to investigate the effect of LUS-guided therapy in patients with acute HF, tested the use of artificial intelligence/machine learning (AI/ML)-based automated guidance systems in order to detect lung congestion.…”
Section: Post-heart Failure Hospitalization Carementioning
confidence: 99%
“…These data confirm the prognostic value of guideline-directed medical therapy optimization in patients hospitalized for HF. [30][31][32][33][34] Figure 1 Variability in decongestive strategies among physicians. ADHF, acute decompensated heart failure; SBP, systolic blood pressure.…”
Section: Acute Heart Failurementioning
confidence: 99%